Managing "mixed" migration to the EU: The challenge of sharing responsibility to protect refugees in the 21st Century - Matthias Lücke (EconPol Forum, 2025)
Worldwide, many people aspire to migrate to the EU for various motives, including persecution at home and better economic prospects in the EU - hence the notion of "mixed" migration. Without restrictions, far more people would migrate to the EU than the EU can or will accommodate. This is true even for individuals who would qualify for asylum in the EU. Therefore, the EU should strive to ensure that persecuted individuals have access to protection (though not necessarily in the EU) while limiting mixed migration to the EU. One way to do this is for the EU to provide financial and policy support for the reception and hosting of refugees and migrants along migration routes, while partner countries curb people smuggling and irregular onward movements. Among EU member states, better responsibility sharing may require a stronger financial and operational EU role in the asylum system, given the public-good nature of refugee protection and open borders within the EU.
Keywords: 330